Evaluation of the position variation of mandibular foramen - Berlińska, Magdalena; Misiejuk, Aleksandra; Komisarek, Oskar (Journal of Education, Health and Sport, 2019)
INTRODUCTION: Mandibular foramen is located on the internal surface of the ramus of the mandible. Through this opening mandibular nerve and vessels enter the mandibular canal. As there are no palpable landmarks that allow determining the position of the mandibular foramen precisely, it is helpful to use radiological imaging methods for this purpose. Mainly X-ray techniques are used, especially panoramic radiograph for its accessibility and wide range of diagnostic applications.Knowledge of the position of the mandibular foramen is essential for the correct and effective performance of the inferior alveolar nerve block, which is one of the most common anaesthesia in dental practice.AIMS: The purpose of the study was to examine and find possible correlations between sex, age, posterior teeth loss and relative localization of the mandibular foramen. SUBJECTS AND METHODS: Selected parameters were measured on 50 digital panoramic radiographic images of 50 patients, including 33 males and 17 females, hospitalized in the Maxillofacial Surgery Ward of the Heliodor Swiecicki Clinical Hospital in Poznan.RESULTS: Localization of the mandibular foramen does not correlate with age, nor the posterior teeth loss and sex has only a slight impact on its vertical location. CONCLUSIONS:Since none of the parameters proved to be particularly useful in predicting the location of the mandibular foramen. The operator should administer inferior alveolar nerve anaesthesia in accordance with standard rules.